AIdeal: Sentience and Ideology - Daniel Estrada (Journal of Social Computing, 2023)
This paper addresses a set of ideological tensions involving the classification of agential kinds, which I see as the methodological and conceptual core of the sentience discourse. Specifically, I consider ideals involved in the classification of biological and artifactual kinds, and ideals related to agency, identity, and value. These ideals frame the background against which sentience in Artificial Intelligence (AI) is theorized and debated, a framework I call the AIdeal. To make this framework explicit, I review the historical discourse on sentience as it appears in ancient, early modern, and the 20th century philosophy, paying special attention to how these ideals are projected onto artificial agents. I argue that tensions among these ideals create conditions where artificial sentience is both necessary and impossible, resulting in a crisis of ideology. Moving past this crisis does not require a satisfying resolution among competing ideals, but instead requires a shift in focus to the material conditions and actual practices in which these ideals operate. Following Charles Mills, I sketch a nonideal approach to AI and artificial sentience that seeks to loosen the grip of ideology on the discourse. Specifically, I propose a notion of participation that deflates the sentience discourse in AI and shifts focus to the material conditions in which sociotechnical networks operate.